Pengaruh Kinerja Keuangan terhadap Simpanan Dana Pihak Ketiga Melalui Nisbah Bagi Hasil (Studi Kasus Bank Umum Syariah di Indonesia Periode 2012-2015) - Ayu Annisa; Isna Yuningsih; Rusliansyah Rusliansyah (AKUNTABEL, 2017)
This study aims to determine the effect of the financial performance of third party funds through revenue sharing on Islamic banks during the period of the first quarter of 2012 until the second quarter 2015. The number of samples in this study are 7 companies, which are taken according to specific criteria banking company sharia is still registered during the observation period 2012-2015 which publishes quarterly financial reports during the study period Then hypothesis testing is done by using partial least square (PLS) 3.2.4. The results showed that a statistically significant effect on the financial performance of third party funds, financial performance significant effect on revenue sharing, profit sharing ratio did not significantly affect third-party funds and financial performance did not significantly affect third-party funds through revenue sharing.Keywords: Third-party funds, ratio of profit sharing, capital adequacy ratio (CAR), Non Performing Financing (NPF), Return on Assets (ROA), Operating Expenses Operating Income (ROA), and Financing to Deposit to ratio (FDR)